Bisoprolol Improves RVEF and Heart Rate in PAH - Nichols, Emma Hitt (MD Conference Express, 2014)
Treatment of idiopathic pulmonary arterial hypertension (PAH) with the β-blocker bisoprolol resulted in decreased heart rate, increased right ventricular ejection fraction (RVEF), and improved quality of life. This article presents data from the Beta-Blocker Therapy in Idiopathic Pulmonary Arterial Hypertension trial [NCT01246037; Van Campen JSJA et al. Am J Respir Crit Care 2014].